Sports Law: Some Introductory Considerations - Miloš Galantić (The Society of Aging and Physical Activity (SAPA), 2016)
With the rise of importance of sport as a social phenomenon in recent decades, more public attention has been paid to the issue of the legal nature of the rules governing social relations in sports. The issue raised above are only a part of a much broader topic that involves questions of relations of a classical Westphalian state and changes in the international community as well as issues of the essence and manifestations of law. The traditional theoretical approach, based on the principles of Westphalian sovereign state and state centralism, does not allow the possibility of existence of sports law because the law does not exist outside of the state. The modern theories of legal pluralism represent a different approach and see one of the most powerful examples of non-state law in sports law. If the concept of the existence of sports law is accepted, it is important to determine its contents. From temporal and quantitative distance, sports organizations are autonomous and main creators of the rules of conduct in sport. However, since the second half of the 20th century the state has had bigger and more important role in the regulation of sport